Predisposing, reinforcing, and enabling factors of trans-positive clinical behavior change: A summary of the literature. Issue 2 (2nd April 2016) - MacKinnon, Kinnon Ross; Tarasoff, Lesley A.; Kia, Hannah
ABSTRACT: Transgender, transsexual, and other gender minority (trans) populations experience numerous health disparities in comparison to cisgender (non-trans) groups. Many trans and gender nonconforming people report interactions with health care providers who lack knowledge about the client's specific health care needs and in some cases discrimination from health care providers, which leads to health care avoidance behaviors and poor health outcomes. Trans-positive health care interventions are necessary in order to improve health care access and outcomes for this marginalized group. In this paper we (a) synthesize literature in the areas of trans-positive care and clinical behavior change according to predisposing, reinforcing, and enabling factors, factors to be addressed as a part of the Precede-Proceed model, a model to develop and evaluate behavior change interventions, and (b) discuss future directions for research and program development with the goal of improving access to competent and quality health care for trans populations.